Efficacy and safety of tirabrutinib monotherapy in relapsed or refractory B-cell lymphomas/leukemia: a meta-analysis - Wang, Jingfei; Cheng, Hai-en; Sun, Yanhua; Li, Zhenfeng; Zang, Yunke; Zhao, Yuying; Yang, Guimao; Liu, Zhijun; Sun, Yaqi; Sun, Yanli (Frontiers in Pharmacology, 2025)
BackgroundTirabrutinib is a potent, irreversible, and highly selective Bruton’s tyrosine kinase (BTK) inhibitor that has demonstrated significant therapeutic activity in patients with relapsed or refractory B-cell lymphoma. However, the safety and efficacy of tirabrutinib monotherapy have not been systematically assessed. This meta-analysis aims to assess the safety and efficacy of tirabrutinib monotherapy in patients with B-cell lymphoma.MethodsWe conducted a comprehensive literature search in Embase, PubMed, Web of Science, and Cochrane Library databases to identify prospective clinical trials evaluating tirabrutinib monotherapy in B-cell lymphoma. Data on efficacy and safety were extracted and analyzed.ResultsA total of seven studies were included in the meta-analysis. The clinical trials primarily involved patients with chronic lymphocytic leukemia (CLL), primary central nervous system lymphoma (PCNSL), mantle cell lymphoma (MCL), and Waldenström’s macroglobulinemia (WM). The pooled overall response rate (ORR) was 72.5%, with complete response (CR) rate of 18.6%, stable disease (SD) rate of 13.8%, and partial response (PR) rate of 41.1%. The highest median progression-free survival (mPFS) was observed in patients with CLL, reaching 38.5 months. Neutropenia was the most common adverse event (AE), both all grades and grade ≥3. Additionally, a high incidence of skin-related AEs was reported.ConclusionTirabrutinib monotherapy demonstrates a manageable safety profile and promising efficacy in patients with B-cell lymphoma. However, these findings need to be confirmed by larger and higher-quality randomized controlled trials in the future. Further research should also explore the long-term effects and potential benefits of combination therapies involving tirabrutinib.Systematic Review RegistrationIdentifier CRD42024552721.